2021
DOI: 10.1177/0950017021999198
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading China through Automation: Manufacturers, Workers and the Techno-Developmental State

Abstract: This article analyses how local states, electronics manufacturers and low-skilled workers perceive and make decisions about automation under China’s techno-developmentalism. Since the early 2010s, local states have made automation – specifically, the substitution of robots for human workers – the linchpin of their techno-developmentalist strategy and set statistical targets to facilitate policy implementation. Although manufacturers realised the limitations of such substitution, most continue to overstate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The fast development and adoption of automation technologies exemplified by automatic vehicles, industrial robots, and artificial intelligence in the past few decades generate significant social and economic implications (Acemoglu and Restrepo, 2019;Lei, 2021). Many existing studies focus on the influence of industrial robots on labor market out of the concern that machines are competing with human beings (Acemoglu and Restrepo, 2021;Acemoglu and Autor, 2011).…”
Section: Literature On the Influence Of Industrial Robotsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fast development and adoption of automation technologies exemplified by automatic vehicles, industrial robots, and artificial intelligence in the past few decades generate significant social and economic implications (Acemoglu and Restrepo, 2019;Lei, 2021). Many existing studies focus on the influence of industrial robots on labor market out of the concern that machines are competing with human beings (Acemoglu and Restrepo, 2021;Acemoglu and Autor, 2011).…”
Section: Literature On the Influence Of Industrial Robotsmentioning
confidence: 99%
“…In addition to the debates relating robots use with employment, wage and income share, the literature also touches upon the economic influence of industrial robots in economic growth (Aghion et al, 2019;Berg et al, 2018), energy consumption (Wang et al, 2022a), productivity (Kromann et al, 2020;Ballestar et al, 2020), technology advance (Liu et al, 2020), and the social impact (Lei, 2021).…”
Section: Literature On the Influence Of Industrial Robotsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Dettmer (2021) found that the implementation of this agreement did not translate into an equally strong role for unions and workers, mainly due to a lack of funding. Lei (2021) argues that in China, automation and the substitution of robots for human workers is an essential strategy for local states as part of the country's techno-developmentalism. Even though manufacturers are aware of the limitations of this substitution, they continue to do so in order to receive material and symbolic benefits from local states.…”
Section: Varieties Of Capitalism Meet the Digital Economymentioning
confidence: 99%
“…Platform workers in countries with weaker independent collective bargaining institutions have more often taken the form of direct worker-organized protests and mobilizations, often coordinated by NGOs or grassroots labour organizations. Research in India (Shalini et al 2021), Brazil (Abilio et al, 2021) and China (Lei 2021;Liu and Friedman, 2021) has shown the central role of both solidarity among the workforce and with the public to these organizing efforts.…”
Section: Union Strategies Towards Digitalizationmentioning
confidence: 99%